Linear Endoscopic Ultrasound Examination of the Biliary System and Its Clinical Applications - Chavan, Radhika; Gandhi, Chaiti; Patel, Maitrey; Solanki, Rushil; Rajput, Sanjay (Journal of Digestive Endoscopy, 2023)
Endoscopic ultrasound (EUS) examination of the biliary system plays pivotal role in pancreatobiliary studies. EUS offers a safe and noninvasive method of the biliary tract disorder evaluation. Although radial EUS provides a straightforward orientation, practicing biliary system examination with a curvilinear echoendoscope is advisable because of its added therapeutic benefits. Linear EUS may pose challenge in understanding the orientation and tracing nondilated bile duct in the beginning. However, adopting a systematic station-wise approach can help in comprehending the orientation and effectively tracing the entire bile duct. In this review, we have discussed linear EUS examination of the bile duct and gallbladder from various stations and its clinical applications.
Keywords: anatomy; common bile duct; endoscopic ultrasound; gallbladder; linear echoendoscope